Analisis January Effect Pada Saham Astra Internasional (ASII) Di Bursa Efek Indonesia Pada Periode 2005 - 2015 - Andreas Kiky (Universitas Multimedia Nusantara, 2016)
In Stock Market our goal is pursue optimum wealth by appreciation of our Stocks. Stock price fluctuate over time as nobody can predict. In this research our aim is to observe the market anomaly that might be happened as the investor behave. We will examine January Effect as Keim observe in 1986 in Indonesia Stock Exchange. Also we can also examine Efficient Market Hypothesis as the result from anomaly and abnormal return that founded in this research. If we can find the market anomaly perhaps we can map the market seasonal trend as the past data recorded. If this anomaly exists we could suggest investor to invest their money as the anomaly data shown. Then investor could gain optimum wealth base on this information. Purpose of this paper is to examine market anomaly and does it exist in Indonesia market? Our main objective is to predict the market movement base on seasonal or anomaly pattern that has been found in previous research. We use CAPM to measure Expected Return of Asset and we use ASII stock price to measure the return of the stock. Our finding is far from our expectation. We expect to find January Effect here but unfortunately we found another anomaly that happen in May and October. Our research suggest that we should cautious for this investor behavior because they seem react as the new information or news appear Keywords: Abnormal Return, January-Effect, Market Anomaly, CAPM, Efficient Market Hypothesis